Bitter Freedom : William Stone's Record of Service in the Freedmen's Bureau - Stone, William, 1842-1897 (Book collections on Project MUSE., 2008)
This title presents a firsthand account of evolving race relations in Reconstruction South Carolina. It is an insightful evaluation of the pivotal role of the Freedmen's Bureau during Reconstruction in war-torn South Carolina as written by a young bureau agent eager to do his part in rebuilding a divided nation.